2020
DOI: 10.3390/pathogens9020087
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cytoplasmic Bacteriocin Compounds Derived from Staphylococcus epidermidis Selectively Kill Staphylococcus aureus, Including Methicillin-Resistant Staphylococcus aureus (MRSA)

Abstract: Staphylococcus aureus (S. aureus) is one of the well-known agents causing atopic dermatitis (AD) in susceptible individuals, and Staphylococcus epidermidis (S. epidermidis) produces class I thermostable bacteriocins that can selectively kill S. aureus, suggesting protective roles against AD. There is a large need for developing precise therapies only to target S. aureus and not to harm the beneficial microbiome. On the agar well diffusion assay, live planktonic S. epidermidis showed clear zones of inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
(41 reference statements)
0
13
0
2
Order By: Relevance
“…Other species apart from S. chromogenes also inhibit the growth of major mastitis pathogens. In a recent study, cytoplasmic bacteriocins from S. epidermidis selectively inhibited growth of S. aureus, including methicillin-resistant strains (112). These studies suggest the need for additional in vivo studies to determine how bacteriocins influence NAS specieslevel interactions in the milk microbiome.…”
Section: Interactions Within the Microbiomementioning
confidence: 99%
“…Other species apart from S. chromogenes also inhibit the growth of major mastitis pathogens. In a recent study, cytoplasmic bacteriocins from S. epidermidis selectively inhibited growth of S. aureus, including methicillin-resistant strains (112). These studies suggest the need for additional in vivo studies to determine how bacteriocins influence NAS specieslevel interactions in the milk microbiome.…”
Section: Interactions Within the Microbiomementioning
confidence: 99%
“…As stated above, since it is thought that the characteristics/abilities (pathogenicity factors) possessed by these microorganisms may play an important role among the factors affecting the relationship between FLA and bacteria living in the same environ- ment, the subject should be investigated in detail. For example, it is known that the S. epidermidis ATCC 12228 strain, which was tested in our study and is avirulent, has molecules called bacteriocin that it releases into the external environment (43). This bacterium thus inhibits some species (eg S. aureus) that live in the same environment and are close to it.…”
Section: Discussionmentioning
confidence: 89%
“…An in vitro study showed that cytoplasmic bacteriocins isolated from S. epidermidis selectively exhibited antimicrobial activity against S. aureus and methicillin-resistant S. aureus (MRSA). These findings suggest that these cytoplasmic bacteriocin compounds could potentially inhibit the growth of S. aureus and be used as a topical AD treatment [ 68 ].…”
Section: Resultsmentioning
confidence: 99%